Factors Affecting Nurses Performance Working in Intensive Care Units at Tertiary Care Hospitals Peshawar: Nurses Performance Working in ICU - Ullah, Ihsan; Ali, Sardar; Hussain, Rashid; Hussain, Akhtar; Iqbal, Muhammad; Rafsoon, .; Sultan, Amir (Pakistan Journal of Health Sciences, 2023)
Specialized nurses play a significant role in the capacity of standard health care across the globe. Many factors in intensive care units (ICUs) are present that could waste nurses’ time and energy. Objectives: To determine the factors affecting job performance of nursing staff working in Peshawar, Khyber Pakhtunkhwa, Pakistan. Methods: In this Descriptive Cross-sectional study, total of 325 nurses were selected through census sampling working in ICUs of five tertiary care hospitals Peshawar from May, 2021 to September 2021. The data collected by using adapted research instrument which had two parts: 1-demographic data, 2-nursing performance factors/obstacles. The data were analyzed with the descriptive and inferential statistics by using SPSS version-22. Results: The most common factors were: delay in getting medications from pharmacy (71.79%), improper patient’s beds space in ICUs (69.55%), distraction caused by the family’ members (62.82%) and insufficient space to sit down and do paper-work (57.69%). In the field of technology shortage of equipment’s (52.56%) and using equipment’s in poor condition (41.7%) were the most frequent obstacles. Gender, age and specialization in ICU is associated with factors that affect the performance of ICU nurses. Conclusions: Many obstacles such as delay in getting medication from pharmacy and having to use equipment in poor condition can be managed by simple interventions such as implementation of centralized pharmacy system as well as biomedical engineering system. Furthermore, management of policies and enhancing teamwork are needed to reduce obstacles such as inadequate information from physicians and disorganized unit.